2020
DOI: 10.1016/j.jcot.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Closed vs open reduction in developmental dysplasia of the hip: The short-term effect on acetabular remodeling

Abstract: Background: This study aims to assess acetabular remodeling following closed vs, open hip reduction in children younger than 2 years of age. Methods: Records of children with DDH, who underwent closed or open reduction, were reviewed. Acetabular index (AI) was measured on radiographs taken prior to reduction and on outcome radiographs taken at age 4 years. Radiographic outcomes were analyzed and residual dysplasia (outcome AI 30) degrees recorded. Results: 42 hips had closed reduction; and 26 hips had open red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Contrary to prior reports by Morris et al 7 and Abousamra et al, 11 we did not observe a significant effect of reduction type (open vs. closed) on residual dysplasia. This indicates the clinical effectiveness of both open and closed reduction in patients with DDH at our institution.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to prior reports by Morris et al 7 and Abousamra et al, 11 we did not observe a significant effect of reduction type (open vs. closed) on residual dysplasia. This indicates the clinical effectiveness of both open and closed reduction in patients with DDH at our institution.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent report by Morris et al 7 demonstrated a 41% rate of secondary surgery requirement in patients followed until 10 years of age after open or closed reduction, comparable to prior published rates by Bolland et al (35%) 8 and Luhmann et al (58%). 9 Several studies have attempted to identify risk factors for residual dysplasia in these patients with reports indicating that preoperative femoral head coverage on anteroposterior radiographs, 10 reduction technique (open vs. closed), 8,11 and age at time of reduction 7,12,13 all impact the future development of the hip. In addition, several reports exist regarding the influence of limbus morphology 14,15 and the labrochondral complex, 16 as assessed on postoperative magnetic resonance imaging (MRI), leading to higher rates of residual dysplasia in the short-term.…”
mentioning
confidence: 99%
“…In this study, those treated without a pelvic osteotomy at the time of index reduction had double the risk of developing RAD (78.0% at 2 years) as those treated with an osteotomy (39.0% at 1 year). These rates are much higher than previous reports, which more often have shown rates of RAD around 20% with a follow-up period of 1-2 years 20,31. However, these analyses did not use age-adjusted acetabular index values for defining RAD and often relied on rates of further corrective surgery, the indications for which are largely subjective.…”
Section: Discussionmentioning
confidence: 80%
“…These rates are higher than previous reports, which more often have shown rates of RAD around 20% with a follow-up period of 1-2 years. 20,31 However, these analyses did not use ageadjusted acetabular index values for defining RAD and often relied on rates of further corrective surgery, the indications for which are largely subjective. Notably, among patients without an osteotomy, the average age at open reduction did not differ between those who did and did not develop RAD.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the dearth of reliable evidence-based research that compares CR and OR and the lack of homogeneity among patients in previous cohorts. [13,14] Within the author's clinical unit, some physicians accept CR that is safe (hip abduction < 65˚ that can maintain reduction) and stable (safe zone > 30˚) [15], whereas others only accept complete concentric reduction whose MDP is less than 2mm [11,12] on the intraoperative radiography for children aged 6-24 months with DDH. Therefore, some patients with DDH who underwent safe and stable CR required subsequent OR due to widening of the joint space.…”
Section: Introductionmentioning
confidence: 99%